Promoting Sustainable and Healthy Diets to Mitigate Food Insecurity Amidst Economic and Health Crises in Lebanon - Hwalla, Nahla; Jomaa, Lamis; Hachem, Fatima; Kharroubi, Samer; Hamadeh, Rena; Nasreddine, Lara; Naja, Farah (Frontiers in Nutrition, 2021)
Abstract Introduction: Lebanon, a middle-income Eastern Mediterranean country, continues to face detrimental economic, health and socio-political challenges that are further exacerbated by the COVID-19 pandemic. In parallel, the country has been experiencing a remarkable nutrition transition that has contributed to the burden of malnutrition and non-communicable diseases, all imposing serious repercussions on people’s livelihoods, food security, and health. Such circumstances have prodded public demand for guidance on affordable, healthy, and sustainable dietary choices to alleviate the burden to this emerging unfortunate situation. Objective: The purpose of this study is to provide evidence-based sustainable and healthy dietary recommendations which balance the tradeoffs among the health, environmental footprint and cost dimensions of sustainability, while closely resembling the usual food consumption pattern. Methodology: Data from the latest available national food consumption survey was used as the usual food consumption pattern of Lebanese adults. Optimized dietary patterns were calculated using the optimization model Optimeal which produced patterns most similar to the usual diet and simultaneously satisfying the three main sets of constraints: health, environmental footprints, and cost.The identified healthy and sustainable dietary options were vetted by multiple key stakeholders from the government, academia, international and national nongovernmental organizations. Results: Compared to the usual intake, the optimized diet included higher intakes of whole grain bread, dark green vegetables, dairy products, and legumes, and lower intakes of refined bread, meat, poultry, added sugars, saturated fat, as compared to usual national mean consumption. The optimized dietary model resulted in a decrease in the associated environmental footprints: water use (-6%); and GHG (-22%) with no change in energy use. The cost of the optimized diet was not different from that of the usual intake. Conclusion: An evidence-based sustainable and healthy diet was developed for Lebanon providing the population and policy makers with some answers to a complex situation. Findings highlight the need for the development of sustainable food based dietary guidelines for Lebanon to promote diets that are healthy, sustainable, culturally acceptable and affordable and that can alleviate food insecurity among the general population.